How do children solve Aesop's Fable? - Lucy G Cheke (Public Library of Science (PLoS), 2012)
Studies on members of the crow family using the "Aesop's Fable" paradigm have revealed remarkable abilities in these birds, and suggested a mechanism by which associative learning and folk physics may interact when learning new problems. In the present study, children between 4 and 10 years of age were tested on the same tasks as the birds. Overall the performance of the children between 5-7-years was similar to that of the birds, while children from 8-years were able to succeed in all tasks from the first trial. However the pattern of performance across tasks suggested that different learning mechanisms might be being employed by children than by adult birds. Specifically, it is possible that in children, unlike corvids, performance is not affected by counter-intuitive mechanism cues.